2003
DOI: 10.1099/ijs.0.02299-0
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium shottsii sp. nov., a slowly growing species isolated from Chesapeake Bay striped bass (Morone saxatilis)

Abstract: NoteMycobacterium shottsii sp. nov., a slowly growing species isolated from Chesapeake Bay striped bass (Morone saxatilis)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 10 publications
2
75
0
Order By: Relevance
“…Shojaei et al 2000, Cousins et al 2003. Aquatic poikilotherms in particular have been a productive source of novel Mycobacterium spp., including M. montefiorense from moray eels Gymnothorax funebris (Levi et al 2003), M. shottsii and M. pseudoshottsii from striped bass Morone saxatilis (Rhodes et al 2003(Rhodes et al , 2005, M. stomatepiae from the cichlid Stomatepia mariae (Pourahmad et al 2008), and M. salmoniphilum from salmonids, a revived species name which was recently differentiated from M. chelonae (Whipps et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Shojaei et al 2000, Cousins et al 2003. Aquatic poikilotherms in particular have been a productive source of novel Mycobacterium spp., including M. montefiorense from moray eels Gymnothorax funebris (Levi et al 2003), M. shottsii and M. pseudoshottsii from striped bass Morone saxatilis (Rhodes et al 2003(Rhodes et al , 2005, M. stomatepiae from the cichlid Stomatepia mariae (Pourahmad et al 2008), and M. salmoniphilum from salmonids, a revived species name which was recently differentiated from M. chelonae (Whipps et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…At the present, Mycobacterium marinum, M. fortuitum and M. chelonae (Sneath et al, 1986;Frerichs, 1993) in the genus Mycobacterium are known as fish pathogens (Chen et al, 1997;Heckert et al, 2001) and M. marinum sometimes causes skin disease in human (Lim et al, 2000). In addition, Heckert et al (2001), Rhodes et al (2003) and Rhodes et al (2005) reported new species, M. chesapeaki, M. shottii, and M. pseudoshottii, respectively, from striped bass Morone saxatilis in Chesapeake Bay. Levi et al (2003) also reported a new species, M. montefiorense from captive moray eels Gymnothorax funebris and G. moringa.…”
mentioning
confidence: 99%
“…Ucko et al (16) used sequences of almost the entire 16S rRNA gene to characterize and seek heterogeneity of M. marinum strains isolated in Israel and other geographical regions. Furthermore, sequence analysis of this gene has been used to analyse several novel aquatic mycobacteria species (21)(22)(23). However, in these studies only a few species were included.…”
Section: Discussionmentioning
confidence: 99%